A New Species Hexacanalis ashae N.Sp. (Eucestoda: Lecanicephalidae, Braun, 1906) from Trygon zugei at Bombay, (M.S.), India - Khamkar, D.D. (Recent Research in Science and Technology, 2011)
The worm under description deals with new species of genus Hexacanalis ashae n.sp. and after going through the literature in having testes number 50-55 (52), comes closer to H. zugeii, H. yamagutti & H. trygoni but it differs from them in many characters as in position of suckers, size, position and number of testes, shape of ovary, position of vagina, position of genital pores and in shape and position of vitellaria.